Building and maintenance of roads on agricultural research farms - Couper, D.C. (1995)
Good roads can prevent costly damage to machinery. Erosion of roads can be avoided by proper design and construction. Earth roads require continuous maintenance. Maintenance is easy if carried out correctly and routinely.